PENGARUH KOMITMEN ORGANISASI PADA KINERJA MANAJERIAL DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI - Widyawati, Ida Ayu; Sari, Maria M. Ratna (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
This research aimed to determine the effect of organizational commitment on managerial performance, and to determine the ability of a locus of control as moderating to influence of organizational commitment on manajerial performance. 44 samples used with purposive sampling as the method of sampling.The analysis technique used is a simple linear regression, and moderating regression analysis (MRA). This research showed that organizational commitment has significant positive on managerial performance. The research also indicates that the locus of control to moderate the influence of organizational commitment on managerial performance, but give a negative result..
Keywords: organizational commitment, locus of control, managerial performance